Trypanosoma brucei genomics and the challenge of identifying drug and vaccine targets - Agbo, E.C.; Majiwa, Phelix A.O.; Bascher, P.; Claassen, E.; Marinus, F.W.P. (Elsevier, 2003)
There have been tremendous advances in our knowledge of trypanosome biology, yet many aspects remain unclear. Currently, the genome of Trypanosome brucei is being sequenced and this, with other genome-wide analysis methods, could provide novel insights into the parasite and facilitate the development of effective controls. An important new challenge investigators face is how to exploit the information in studying a parasite with so many genetic peculiarities. Here, we summarize our current understanding of molecular genetics of T. brucei and attempt to link genome analysis to the prospects for identifying possible targets for vaccines, novel drugs and specific diagnostics. The value of newly developed genotyping approaches in accelerating these processes is discussed.